Imagining New Possibilities Through Participatory Qualitative Methods - Hayley Weddle; Gabrielle Oliveira (International Journal of Qualitative Methods)
Across a range of disciplines, researchers are employing participatory approaches to better align studies with community needs. For example, a growing body of education scholarship has outlined the value of research-practice partnerships as venues for addressing urgent problems of practice. While such partnerships represent a promising strategy for advancing equity, effective collaboration across research and practice is complex to realize. In this paper, we examine data from two partnership projects to identify strategies for actualizing participatory qualitative methods. Collaborative analysis across our projects revealed possibilities related to three strands of qualitative partnership research: gaining and sustaining access to politically complex spaces, maintaining authentic reciprocity, and making meaning across data. Within each strand, we offer in-depth examples and considerations for researchers across a range of disciplines about how to foster partnerships that promote equitable transformation. As opposed to being prescriptive, we hope to spur reflection across participatory qualitative research teams and support shifts towards more imaginative and humanized methods.